Model Penelitian Kebijakan Kualitatif Tohardi - Ahmad Tohardi (JPASDEV : Journal of Public Administration and Sociology of Development, 2020)
AbstractThe Policy Research Model that uses the quantitative approach is more complicated and commonly used by a quantitative paradigm. Therefore, there must be the other alternative methods that simpler, more pragmatic, and effective methods but without decreasing the scientific values. In this paper, The researcher suggest that a qualitative research model called the Tohardis qualitative research model abbreviated as MPKKT. MPPKKT is designed by the conventional or classic model. They are 1. Pre survey using the naturalistic model in exploring the various problems., 2. Focus Group Discussion (FDG-1) is as a research formulating, 3. Focus Group Discussion (FGD-2) is as a policy formulation, 4. Expert Judgment is as an evaluation of an eligibility policy, 5. Discussion with the stakeholders in considering the policy output to implement it. MPKKT has been applied on the thesis research by the postgraduate students in Magister Program of Social Sciences in Fisip Untan. Based on the above application, here can be inferred that simple and more practical in implementing it. Besides, because it is used the social policy paradigm, it has a highly probability in implementing it by the users. Key words: Policy Research, The Tohardis Qualitative Policy Research Model (MPKK).